Sepsis-induced long-term immune paralysis – results of a descriptive, explorative study. Issue 1 (December 2016) - Arens, C.; Bajwa, S.; Koch, C.; Siegler, B.; Schneck, E.; Hecker, A.; Weiterer, S.; Lichtenstern, C.; Weigand, M.; Uhle, F.
Abstract Background Long-lasting impairment of the immune system is believed to be the underlying reason for delayed deaths after surviving sepsis. We tested the hypothesis of persisting changes to the immune system in survivors of sepsis for the first time. Methods In our prospective, cross-sectional pilot study, eight former patients who survived catecholamine-dependent sepsis and eight control individuals matched for age, sex, diabetes and renal insufficiency were enrolled. Each participant completed a questionnaire concerning morbidities, medications and infection history. Peripheral blood was collected for determination of i) immune cell subsets (CD4+, CD8+ T cells; CD25+ CD127- regulatory T cells; CD14+ monocytes), ii) cell surface receptor expression (PD-1, BTLA, TLR2, TLR4, TLR5, Dectin-1, PD-1 L), iii) HLA-DR expression, and iv) cytokine secretion (IL-6, IL10, TNF-α, IFN-γ) of whole blood stimulated with either α-CD3/28, LPS or zymosan. Results After surviving sepsis, former patients presented with increased numbers of clinical apparent infections, including those typically associated with an impaired immune system. Standard inflammatory markers indicated a low-level inflammatory situation in former sepsis patients. CD8+ cell surface receptor as well as monocytic HLA-DR density measurements showed no major differences between the groups, while CD4+ T cells tended towards two opposed mechanisms of negative immune cell regulation via PD-1 and BTLA. Moreover, the post-sepsis group showed alterations in monocyte surface expression of distinct pattern recognition receptors; most pronouncedly seen in a decrease of TLR5 expression. Cytokine secretion in response to important activators of both the innate (LPS, zymosan) and the adaptive immune system (α-CD3/28) seemed to be weakened in former septic patients. Conclusions Cytokine secretion as a reaction to different activators of the immune system seemed to be comprehensively impaired in survivors of sepsis. Among others, this could be based on trends in the downregulation of distinct cell surface receptors. Based on our results, the conduct of larger validation studies seems feasible, aiming to characterize alterations and to find potential therapeutic targets to engage.